2017
DOI: 10.1108/bfj-06-2016-0286
|View full text |Cite
|
Sign up to set email alerts
|

Information used in food shoppers’ vegetable purchasing decisions in Chinese societies

Abstract: Purpose The purpose of this paper is to reveal influential information used in vegetable purchasing decisions of household primary food shoppers in China and in Taiwan. Design/methodology/approach Two in-person surveys were administrated separately in Shanghai, China and in Taipei, Taiwan, the two most populous metropolitan areas in China and in Taiwan, respectively. Findings Results reveal that about 32 per cent of respondents in Taipei purchase vegetables once in every two to three days. The majority of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
1
3
0
1
Order By: Relevance
“…Brand/origin and color/size were identified as the buyers' dimensions of a theoretical formative latent construct of the purchasing decision quality of vegetables, fruits, or both, at grocery stores in Slovenia. The identified dimension (brand, origin, packaging, nutrition) in this research is very similar to the dimension (brand, origin, packaging) in Hsu et al (2017) research for the city of Taipei. The advice to producers is to create their own brands or extensively strengthen the existing ones.…”
Section: Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…Brand/origin and color/size were identified as the buyers' dimensions of a theoretical formative latent construct of the purchasing decision quality of vegetables, fruits, or both, at grocery stores in Slovenia. The identified dimension (brand, origin, packaging, nutrition) in this research is very similar to the dimension (brand, origin, packaging) in Hsu et al (2017) research for the city of Taipei. The advice to producers is to create their own brands or extensively strengthen the existing ones.…”
Section: Resultssupporting
confidence: 76%
“…The 13 used attributes were: country of origin, brand, packaging, convenient location, seasonal vegetables, variety in selection, color, appropriate size, nutrition, freshness, residuals, price mark down, and reasonable prices. Except freshness (Ragaert et al, 2004;Peneau et al, 2009;Qing et al, 2012), appropriate size and color (Poole and Baron, 1996), all the attributes were used by Hsu et al (2017). 11 questions of the attributes were measured on a 5-point Likert scale (from 1 -strongly disagree to 5 -strongly agree).…”
Section: Methodology Datamentioning
confidence: 99%
See 1 more Smart Citation
“…A review of previous research on the vegetable circulation channel indicates that most of these studies are mainly focused on the circulation efficiency and consumption (Hsu et al , 2017; Bond et al , 2009; Li and Mu, 2017). Although the initial end of the supply chain (production) is initially important to ensure the high quality and stable supply of vegetables in Beijing, studies on vegetable producers are rarely reported.…”
Section: Introductionmentioning
confidence: 99%
“…(Srinivasan et al, 2004;Verdú Jover et al, 2004). Mientras que entre los extrínsecos sobresalen el nombre de la marca, el precio, el país origen, las etiquetas de información nutricional y la descripción del producto en un amplio rango de condiciones, la alta calidad, estándares de control de calidad, cultivo, origen (zona geográfica a donde pertenece), proceso, empaquetado, medio ambiente sustentable y la promoción, donde destacan las rebajas de precio y el precio razonable (Hsu et al, 2017;Nassivera et al, 2020;Okamoto & Dan, 2013).…”
unclassified